The Effect of Spirituality on The Fear of Pre-Operation Patients at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga - Rochmah Oktavia; Jebul Suroso; Agus Santosa; Tina Muzaenah (Viva Medika, 2024)
Surgery is an action carried out by opening or exposing a part of the body through an incision and ending with stitching the wound. This surgical action can cause anxiety in the patient so that the patient feels uncomfortable and even feels threatened. This may influence a person's spiritual level. Spirituality is something important for every individual in their relationship with God Almighty. This research was conducted to determine the effect of the patient's level of spirituality on the pre-operative anxiety level of patients in the Dahlia ward at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The design of this research is quantitative with a cross-sectional approach. The samples used were pre-operative patients in the Dahlia ward at RSUD dr. R. Goeteng Taroenadibrata Purbalingga with 60 respondents using Purposive Sampling techniques. The research instrument used a spirituality level questionnaire and an anxiety level questionnaire. Data analysis uses the Chi-Square Test. The research results showed (1) the majority of pre-operative respondents in the Dahlia ward were aged 26-45 years, female, self-employed, had at least elementary school education, and the type of general surgery; (2) the majority of preoperative patients' spirituality level is moderate and the anxiety level of surgical patients is not anxious; (3) there is an influence of the patient's spirituality level on the anxiety level of pre-operative patients in the Dahlia ward at Dr. RSUD. R. Goeteng Taroenadibrata Purbalngga with a p-value of 0.025. The urgency of this study lies in the importance of understanding the influence of spirituality on anxiety in the context of preoperative care, because unmanaged anxiety can impact the success of surgery and patient recovery. This study contributes to health science by providing evidence that spirituality can be one approach to reducing preoperative patient anxiety. The level of spirituality has a significant effect on the level of preoperative patient anxiety. Therefore, it is recommended that health workers integrate a spiritual approach into preoperative patient care, such as providing spiritual support, counseling sessions, or facilities for worship. This strategy is expected to increase the patient's psychological comfort, thereby supporting the success of medical procedures and the recovery process.